3-D seismic velocity structure of the Kumaun–Garhwal (Central) Himalaya: insight into the Main Himalayan Thrust and earthquake occurrence. Issue 1 (30th October 2021) - Gupta, Sandeep; Mahesh, P; Kanna, Nagaraju; Sivaram, K; Paul, Ajay
SUMMARY: Objective assessment of seismic hazard and understanding of the Himalayan arc's tectonics requires detailed information on the crustal structure and geometry of the underthrusting Indian Plate beneath the Himalaya. Here, we present high-resolution 3-D P- wave velocity ( V p ) and P -to- S -wave velocity ratio ( V p / V s ) images of the Kumaun–Garhwal Himalaya, a proposed potential region for the future great earthquake. We generate these images by inverting arrival times of 515 local earthquakes recorded by 41 broad-band stations during November 2006–June 2008. The tomographic images show a heterogeneous structure in the upper-mid crust. These images, along with available geophysical and geological information, indicate the presence of quartz-rich felsic rocks in the uppermost crust and the occurrence of saline-rich aqueous fluid/partial melt in the upper-mid crust. We propose that the Main Himalayan Thrust (MHT), having a flat-ramp-flat geometry, lies at the base of these fluid zones. The small- and moderate-to-strong-magnitude earthquakes are mainly confined to the fluid-rich zones along the MHT and quartz-rich rocks in the upper crust. Such an interpretation implies that the earthquake occurrence in the Kumaun–Garhwal Himalaya is largely controlled by the geometry of the MHT and crustal lithology.